Petrogenesis of the volcanic suite of Bouvetøya (Bouvet Island), South Atlantic - Prestvik, Tore; Goldberg, Steven; Goles, Gordon G. (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1999)
Whole rock and mineral compositions of volcanic rocks collected during the Norwegian Polarsirkel expedition (1978/79) to the volcanic istand of Bovetøya (close to the Bouvet Triple Junction) are discussed and compared with previously published data from the island. The rock types, hawaiite, benmoreite, and peralkaline trachyte and rhyolite (comendite) are related to each other by crystal fractionation processes. The trace element and radiogenic isotope signatures displayed by the Bouvetøya rocks are those of a moderately enriched oceanic island suite. On several isotope plots Bouvetøya rocks fall on or close to mixing lines between the euriched EM-l and HIMU mantle components. Mixing between depleted morb mantle (DMM) and euriched components is not likely. Thus, Bouvetøya displays a typical plume signature.
Publisher: [Routledge]
Keywords: Bouvetøya; M/V Polarsirkel; NARE 1978/79; geokjemi; geologi; petrologi

Levels and interactions of heavy metals in sea birds from Svalbard and the Antarctic - Norheim, Gunnar (Environmental Pollution (Barking, Essex: 1987), 1987)
Samples of liver and kidney from 92 seabirds of ten species collected on Spitsbergen and in the Antarctic, were analysed for their content of copper, zinc, cadmium, lead, mercury and selenium. Significantly higher levels of copper and zinc were observed in birds from Spitsbergen than in those from the Antarctic, while the opposite was true for selenium. The highest cadmium levels were found in fulmar Fulmarus glacialis and macaroni penguin Eudyptes chrysolophus. A possibility of kidney damage due to cadmium exists. The highest mercury levels were recorded in brown skua Catharacta lonnbergi collected at Bouvetøya. Lead was not detected in any of the birds. Significant correlations were observed between levels of several of the metals studied, especially between cadminum and zinc and between mercury and selenium. However, for all birds, the highest correlation coefficients were observed when the molar concentrations of cadmium plus mercury, and selenium plus zinc, were used in the calculations. Thus several protective mechanisms may operate to diminish effects of heavy metal contaminants.
Keywords: Bouvetøya; Dronning Maud Land; NARE 1976/77; NARE 1978/79; forurensning; fugler; miljøgifter; ornitologi

Bryophytes of Bouvetøya - Bell, Graham B; Blom, Hans H (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; moser

General outline of the botanical investigations on Bouvetøya - Engelskjøn, Torstein (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner

Phytogeographical relations of the cryptogamic flora of Bouvetøya - Engelskjøn, Torstein; Jørgensen, Per Magnus (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; lav

Absolute movements, mass balance and snow temperatures of the Riiser-Larsenisen Ice Shelf, Antarctica - Gjessing, Yngvar; Wold, Bjørn (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; geofysikk; glasiologi; isshelf

Macrolichens of Bouvetøya - Jørgensen, Per Magnus (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; lav

The supralittoral, freshwater and terrestrial algal vegetation of Bouvetøya - Klaveness, Dag; Rueness, Jan (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; alger; botanikk

Flow and thickness of Riiser-Larsenisen, Antarctica - Orheim, Olav; Drewry, David (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; glasiologi; isshelf

Oxygen isotopes and accumulation rates at Riiser-Larsenisen, Antarctica - Orheim, Olav; Gjessing, Yngvar; Lunde, Torbjørn; Repp, Kjell; Wold, Bjørn; Clausen, Henrik B; Liestøl, Olav (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; geofysikk; glasiologi; isshelf

Hydrolysis of proteins by peptide hydrolases of Antarctic krill, Euphausia superba - Osnes, Knut Kristian; Ellingsen, Trond E.; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1986)
1. The hydrolysis of casein by peptide hydrolases of Antarctic krill, E. superba, has been 2. The peptide hydrolases studied included trypsin-like enzymes, carboxypeptidase A-type of enzymes, carboxypeptidase B-type of enzymes, and an aminopeptidase isolated from Antarctic krill. 3. The trypsin-like enzymes seemed to play a decisive role in the degradation of casein, whereas the carboxypeptidase A, carboxypeptidase B and the aminopeptidase had limited effect when acting on casein alone. When combined with the trypsin-like enzymes, the exopeptidases effected enhanced release of amino acids from the protein. 4. Based on the pattern of amino acids relased from casein by a crude extract of krill, and by the isolated peptide hydrolases either alone or in combination, it is concluded that the purified peptide hydrolases examined comprise the major enzymes responsible for the autoproteolytic activity of krill at neutral- to weakly alkaline pH.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

On the purification and characterization of exopeptidases from Antarctic krill, Euphausia superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1986)
1. Two carboxypeptidase-A type of enzymes and two carboxypeptidase-B type of enzymes effecting hydrolysis of Hipp-l-Phe and Hipp-l-Arg respectively, have been purified from E. superba using gel filtration, affinity chromatography and FPLC-anion exchange chromatography. In addition an aminopeptidase has been partly purified. 2. The carboxypeptidases had mol. wts of 27,000 (carboxypeptidase A) and 31,000 (carboxypeptidase B). 3. Carboxypeptidase A exhibited a broad pH optimum with a maximum at pH 5.5–6.5, whereas carboxypeptidase B had a more narrow pH-optimum with a maximum at pH 7. The aminopeptidase had an optimum at about pH 8.7. 4. The carboxypeptidases were inhibited by the chelating agent 1,10-phenanthroline.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Crustose lichens of Bouvetøya - Øvstedal, Dag Olav (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; lav

Lichencolous ascomycetes from Bouvetøya - Øvstedal, Dag Olav; Hawksworth, David L (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; lav

Lamprospora miniatopsis Spooner, a bryophilous discomycete from Bouvetøya - Schumacher, Trond (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; moser

Seismic investigations in the Weddell Sea Embayment - Haugland, Kristen; Kristoffersen, Yngve; Velde, Anders (Tectonophysics, 1985)
Keywords: Antarktis; NARE 1976/77; NARE 1978/79; Weddellhavet; ekspedisjoner; seismologi

Peptide hydrolases of Antarctic krill, Euphausia superba - Osnes, Knut Kristian (Norwegian Institute of Technology, University of Trondheim, 1985)
Publication Title: Department of Biochemistry ISBN: 8272450119
Keywords: Antarktis; NARE 1978/79; Sørishavet; biokjemi; fiskeprodukter; krill; lyskreps; marin biologi; peptider

On the purification and characterization of three anionic, serine-type peptide hydrolases from antarctic krill, Euphausia Superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. Three enzymes effecting hydrolysis of TAME have been purified from E. superba using gel filtration, affinity chromatography and FPLC-anion exchange chromatography. 2. The enzymes had molecular weights of 30,000 (Enzyme I), and 31,000 (Enzymes II and III), respectively, as estimated from SDS-PAGE. 3. pH-optima of about 8.2 were observed for all three enzymes. 4. The enzymes were inhibited by phenyl methyl sulphonyl fluoride (PMSF), tosyl lysyl chloromethyl ketone (TLCK) and soybean trypsin inhibitor (SBTI), whereas tosyl phenyl chloromethyl ketone (TPCK) had no effect on the activity. 5. The enzymes were stable at neutral pH, and only slowly inactivated at highly alkaline pH. Low pH rapidly inactivated all three enzymes. 6. Enzyme I liberated amino acids from casein, whereas Enzymes II and III did not; the latter two being true endopeptidases which effected enhanced amino acid production from casein when mixed with Enzyme I.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Peptide hydrolases of Antartic krill, Euphausia superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. A survey has been made of the peptide hydrolase activities occurring in Antarctic krill, Euphausia superba. 2. A major protein hydrolyzing activity in the pH range of 6–8, and a minor activity at pH 3–4, were detected. 3. Temperature optima of approx. 50°C and 35–40°C, respectively were determined for the neutral and acid peptide hydrolases. 4. Trypsin-like activity, as well as carboxypeptidase A-, carboxypeptidase B-, and aminopeptidase activity were detected in extracts of krill. 5. Considerable variation in total hydrolase activity was observed in different catches of E. superba obtained from the same area. 6. The pattern of release of amino acids during autolytic breakdown of krill proteins was very similar in catches of krill exhibiting considerable differences with respect to total peptide hydrolase activity.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Lipids in Antarctic krill : composition and post mortem changes - Ellingsen, Trond E; Mohr, Viggo (1982)
Publication Title: Norwegian Antarctic Research Expeditions 1976/77 and 1978/79
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; biokjemi; krill; lipider; lyskreps; marinbiologi; plankton

A microearthquake survey of Bouvet Island, South Atlantic - Kristoffersen, Yngve; Bungum, Hilmar (Tectonophysics, 1982)
A microearthquake survey carried out during the 1978–1979 Norwegian Antarctic Research Expedition indicates that only minor seismic activity is associated with the Bouvet volcano.
Keywords: Bouvetøya; NARE 1978/79; geofysikk; seismologi; vulkaner

Iceberg response to sea state - Orheim, Olav; Wadhams, Peter; Kristensen, Monica (Iceberg research, 1982)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; ekspedisjoner; forskning; isberg; isfjell; målinger

The seismicity of the Bouvetøya region - Bungum, Hilmar; Kristoffersen, Yngve; Nilsen, Alf K. (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; seismologi; vulkaner

Enzyme polymorphism in Antarctic krill (Euphausiacea); genetic variation between populations and species - Fevolden, Svein Erik; Ayala, Fransisco J. (Sarsia, 1981)
By means of enzyme electrophoretical assays three samples of Euphausia superba, all from the Atlantic sector of the Antarctic Ocean, were examined to see whether or not they represent genetically separated populations. The same samples were also compared with E. superba from off the Western coast of the Antarctic Peninsula, representing the Pacific sector. The latter animals have previously been studied by other authors. One sample of a second species of Antarctic krill, E. crystallorophias, was likewise examined. Thirty-five loci were studied in E. superba, and it is concluded that the three samples from the Atlantic sector most probably do not represent reproductively isolated populations. Their average heterozygosity, about 10%, is however greater than the value previously found for the ‘Pacific’ E. superba, 5.8 %. Calculations of the genetic identity and genetic distance between the Atlantic and ‘Pacific’ samples of E. superba suggest they represent separate populations. The average heterozygosity of E. crystallorophias was estimated to be between 9.1 and 9.4 %, from studies of 33 loci. The genetic distance between this species and E. superba was estimated at 0.989. The results are finally discussed in terms of postulated theories on genetic variability versus environmental heterogeneity.
Publisher: Taylor & Francis
Keywords: NARE 1976/77; NARE 1978/79; Sørishavet; genetikk; krill; marin biologi; plankton

Hydrographic surveying around Bouvetøya - Fjørtoft, Jon H (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; hydrografi; oseanografi

Measurements of ocean current and bottom pressure near Bouvetøya, January–March 1979 - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; havstrømmer; oseanografi

Geodetic determination of Bouvetøya - Fossum, Bjørn A (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; geodesi

A census of penguins and seals on Bouvetøya - Haftorn, Svein; Sømme, Lauritz; Gray, John S (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; pingviner; seler; zoologi

New map of Bouvetøya - Helle, Sigurd G (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; M/V Polarsirkel; NARE 1976/77; NARE 1978/79; geodesi

Geology of Bouvetøya, South Atlantic - Prestvik, Tore; Winsnes, Thore S. (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; geologi; vulkaner

Supercooling in two Antarctic arthropods from Bouvetøya - Sømme, Lauritz (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Krill off Bouvetøya and in the southern Weddell Sea with a description of larval stages of Euphausia crystallorophias - Fevolden, Svein Erik (Sarsia, 1980)
In the austral summer 1978/79 samples of krill were taken off Bouvetøya and in the southern Weddell Sea. Off Bouvetøya Euphausia superba Dana was the dominant species, but the population pattern indicates that the individuals found there were expatriates from other areas. For the first time larvae of E. superba were found in significant amounts in the southern Weddell Sea. Except from shallow water and the most southern position, they were equal in abundance to the larvae of E. crystallorophias Holt & Tattersall. Larval stages of the latter are described as is the successive spawning that takes place among the three species of krill found in the southern Weddell Sea.
Publisher: Taylor & Francis
Keywords: Bouvetøya; NARE 1978/79; Weddellhavet; dyreplankton; krill; plankton; zooplankton

Flow Around Icebergs - Foldvik, Arne; Gammelsrød, Tor; Gjessing, Yngvar (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; isberg; observasjoner; oseanografi; sjøvann

Measurements of oscillations and flexure of icebergs - Foldvik, Arne; Gammelsrød, Tor; Gjessing, Yngvar (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; havis; is; isbreer

Measurements of the radiation temperature of Antarctic icebergs and the surrounding surface water - Foldvik, Arne; Gammelsrød, Tor; Gjessing, Yngvar (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: NARE 1978/79; Sørishavet; ekspedisjoner; glasiologi; havis; is; isbreer

Studies of icebergs, ice fronts and ice walls using side-scanning sonar - Klepsvik, John O; Fossum, Bjørn A (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; NARE 1978/79; ekspedisjoner; forskning; glasiologi; is; isberg; isfjell; isfront; morfologi; snø

Physical characteristics and life expectancy of tabular Antarctic icebergs - Orheim, Olav (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; isberg; isfjell; isfront; isshelf; kalving; stratigrafi

Botaniske undersøkelser på Bouvetøya : om materialet som ligger til grunn og dets videre bearbeiding - Engelskjøn, Torstein (1979)
Pages: 10 s. + to stensilerte vedlegg Place: [Oslo]
Keywords: Bouvetøya; NARE 1978/79; botanikk; ekspedisjoner

De norske Antarktis-ekspedisjonene 1976-77 og 1978-79: biologiske undersøkelser på Bouvetøya og i havet - Sømme, Lauritz; Fevolden, Svein Erik (Det norske videnskaps-akademi. Årbok, 1979)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biologi; geografi

Forslag til maringeofysiske undersøkelser ved Bouvetøya - Kristoffersen, Yngve ([Norsk Polarinstitutt], 1978)
Pages: [14] s. Publication Title: Antarktisekspedisjonen 78/79 Place: [Oslo]
Keywords: Bouvetøya; NARE 1978/79; marin geofysikk